International HRM in the IJVs: the impacts of interpersonal relationships between employees from different cultural backgrounds on the work performance - Jiang, Cheng (2013)
Purpose: Human resource issues are one of the most significant problems in the management of international joint ventures (IJVs). This study aims to investigate the possible impacts of interpersonal relationships between Chinese employees and foreign employees in China’s Sino-foreign joint ventures on employees’ work performance. At first, this study examines the possible influences of interpersonal relationships between people from different cultural backgrounds on group processes. Then, the probable effects of group processes on the performance of intellectual decision-making work and repetitive manual work are investigated. Methods: Primary data is collected in this study. Self-report questionnaires for employees and telephone interviews with supervisors are used as the methods of collecting data. In total, 51 employees (including 28 Chinese employees and 23 foreign employees) and 5 Chinese supervisors from Sino-foreign joint ventures in China participate in this study. Findings: This study reveals that interpersonal relationships have significant influences on several group processes and some group processes influence the performance of intellectual decision-making work and repetitive manual work significantly. Overall, this study finds that employees working with their foreign friends tend to perform both intellectual decision-making work and repetitive manual work better than employees who work with their foreign acquaintances. Keywords: International HRM, International Joint Ventures, Interpersonal Relationship, Work Performance.